Perilaku Ekonomi dan Dampak Risikonya Bank Syariah di Yogyakarta dalam Pembiayaan Mudarabah dan Murabahah bagi Dana Deposan - azzarqa azzarqa; Abd Mughits (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2014)
This research tries to check the potency of risk of Islamic bank in defrayal of muḍārabah and murābaḥah. This research was inspired from ascription of whereas one who said that the Islamic banks have not been risk because they have owned the guidance of risk management published by Bank Indonesia (BI). One way to assess the existence of potency of risk of Islamic bank in its defrayal product is using the theory of behavioral economics which’s in general differentiated to two categories, that is rational that which tends to be risk and irrasional that which tend to be not risk. Rational behavior is presented by the approach of efficiency market hyphotesis (EMH) and irrational behavior is presented by the approach of adaptive market hypothesis (AMH) And behavioral finance (BF). This research objects are four Islamic banks in Yogyakarta. After conducting by tracing of field data then found that four Islamic banks affirm still face the risk in their operational, especially operational risk, risk of credit and risk of liquidity. Four banks show that their behaviors are irrasional because tend to show the behavior of AMH and BF, than EMH. Thereby its risk potency tends to minimizes to rate of return of clients of deposan or third party lenders (DPK).